Skład pokarmu wilka Canis lupus L. w Wigierskim Parku Narodowym - Mysłajek, Robert; Nowak, Sabina; Romański, Maciej; Tołkacz, Katarzyna (Leśne Prace Badawcze, 2018)
The diet of wolves Canis lupus L. was assessed in the Wigry National Park in North-Eastern Poland, which overlaps with the Natura 2000 site „Ostoja Wigierska”. The content of a total of 149 scat samples was collected in 2017 and analysed in order to determine dietary composition. Wolves primarily feed on wild ungulates, which make up 75.4% of food biomass. Despite the fact that wild boar Sus scrofa L. and red deer Cervus elaphus L. dominate in the ungulate community in the study area, the primary prey species was observed to be roe deer Capreolus capreolus L. with 39.6%, while red deer and wild boar only constituted 18.7% and 8.3% of the food biomass, respectively. Additionally, beaver Castor fiber L. was found to be an important prey (10.9%) as well and livestock accounted for 15.1% of all biomass consumed. The livestock eaten by wolves also included carcasses of domestic animals illegally disposed of in the forest. We therefore conclude that decisions on the management of the wolf’s food base within protected areas, such as national parks or Natura 2000 sites, should be preceded by intensive local studies.